A composite separator for deep cycle power type lead-acid batteries
Patent Information
- Application Number
- CN202310418520.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-19
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-04-19
AI Technical Summary
但是,其不足之处在于所得AGM隔板的吸酸量、毛细吸酸高度均较低,电解液在隔板中的酸分布的均匀性也较低,不利于提升动力电池的循环寿命
(1)通过调整优化粗棉层与细棉层的棉组分、配比以及其在复合隔板中的厚度比例,使得隔板X-Y平面上的毛细管作用调酸的效果达到更佳,同时复合隔板上中下酸的分配均匀性也更好;
Smart Images

Figure BDA0004185837800000051 
Figure BDA0004185837800000061
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of AGM separators, and in particular to a composite separator suitable for deep-cycle power lead-acid batteries. Background Technology
[0002] Currently, AGM separators are an important component of lead-acid batteries, playing a crucial role as the "third electrode." The main functions of AGM separators in batteries include: preventing short circuits between the positive and negative electrodes, storing acid, maintaining acid and heat resistance and chemical stability, maintaining oxygen recombination channels and capillary acid absorption, and maintaining electrode assembly pressure. For power batteries, which are deep-cycle batteries, battery failure often occurs during continuous deep discharge cycles due to the softening and shedding of the positive electrode active material and uneven acid distribution. During this process, the wet-state pressure holding capacity of the electrode group effectively mitigates the softening and shedding of the positive electrode active material. The structure of the positive and negative electrode fibers (pore structure in the XY plane) and the capillary acid absorption capacity (pore size in the Z-direction) determine the acid distribution of the electrolyte within the separator, thus affecting the deep-cycle life of the power battery.
[0003] Chinese invention patent CN 109273642 A discloses a method for preparing a low resistivity AGM separator, including the following steps: (1) glass fiber pretreatment; (2) organic fiber hydrophilic treatment; (3) slurry preparation; (4) molding; (5) conductive treatment; (6) cleaning; (7) post-treatment to obtain the finished AGM separator. However, its shortcomings are that the acid absorption capacity and capillary acid absorption height of the obtained AGM separator are both low, and the uniformity of acid distribution of electrolyte in the separator is also low, which is not conducive to improving the cycle life of power batteries. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a composite separator suitable for deep-cycle power lead-acid batteries. By adjusting the cotton composition of the coarse and fine cotton layers, it ensures that the acid near the positive and negative electrodes is regulated and the acid distribution between the middle and lower parts of the separator is uniform through capillary action on the XY plane, providing sufficient oxygen recombination channels. At the same time, it ensures the rebound performance of the power battery during deep cycling and improves the cycle life of the deep-cycle power battery.
[0005] The objective of this invention is achieved through the following technical solution: This invention provides a composite separator suitable for deep-cycle power lead-acid batteries, comprising a coarse cotton layer and a fine cotton layer; the coarse cotton layer faces the positive electrode of the battery, and the fine cotton layer faces the negative electrode of the battery; the raw materials of the coarse cotton layer include 17°SR glass fiber cotton and 24°SR glass fiber cotton; the raw materials of the fine cotton layer include 44°SR glass fiber cotton and 29°SR glass fiber cotton.
[0006] This invention relates to a composite separator suitable for deep-cycle power batteries. The separator comprises two layers: a coarse cotton layer and a fine cotton layer. The coarse cotton layer is positioned close to the positive electrode, while the fine cotton layer is positioned close to the negative electrode. By adjusting the cotton composition of the coarse and fine cotton layers, capillary action is used to ensure uniform acid distribution near the positive and negative electrodes and a balanced acid distribution across the separator's upper and lower sections on the XY plane. This provides ample oxygen recombination channels and ensures the battery's resilience during deep-cycle operation, thereby improving the cycle life of the deep-cycle power battery.
[0007] The fine cotton layer has a strong capillary acid absorption capacity. The liquid on the upper layer of the fine cotton will fall laterally into the appropriate pore size of the coarse cotton layer. The coarse cotton layer has a poor acid absorption capacity and will fall to the bottom layer under the influence of weight. Then it will be absorbed by the fine cotton layer to form an acid cycle, which can regulate the uniformity of acid distribution in the middle and lower parts of the composite partition.
[0008] Preferably, the raw material of the coarse cotton layer comprises 39-49% 17°SR glass fiber cotton and 25-30% 24°SR glass fiber cotton by weight percentage.
[0009] The cotton ratio of the coarse cotton layer can increase its liquid retention capacity on the positive electrode side, while improving its high wet resilience performance during cycling.
[0010] Preferably, the raw material of the coarse cotton layer comprises 6-8% reinforcing fibers by weight percentage. The reinforcing glass fibers are glass fibers with a diameter of 9 μm.
[0011] Reinforcing fibers can increase the strength of coarse cotton surfaces.
[0012] Preferably, the maximum pore size of the coarse cotton layer is 42–45 μm.
[0013] Preferably, by weight percentage, the raw material of the coarse cotton layer includes 20-30% fine cotton layer raw material or recycled material, wherein the recycled material is the product of recycled composite partitions after being recycled.
[0014] Recycled materials refer to the process of recycling scrapped partitions from the production process. Recycled materials generally contain fine cotton components, which increases the fine cotton layer content on the coarse cotton surface.
[0015] Preferably, the raw material of the fine cotton layer comprises 40-44% 44°SR glass fiber cotton and 50-54% 29°SR glass fiber cotton by weight percentage.
[0016] Preferably, the raw material of the fine cotton layer comprises 2-4% PET fiber by weight percentage.
[0017] Preferably, the raw material of the fine cotton layer comprises <6% reinforcing fiber by weight percentage.
[0018] Preferably, the pore size of the fine cotton layer is 12–15 μm.
[0019] Preferably, the thickness of the fine cotton layer accounts for 1 / 3 to 1 / 2 of the total thickness of the composite partition.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) By adjusting and optimizing the cotton composition, ratio and thickness ratio of the coarse cotton layer and the fine cotton layer in the composite partition, the capillary effect of acid adjustment on the XY plane of the partition is better, and the uniformity of acid distribution in the middle and lower parts of the composite partition is also better. (2) The composite separator has excellent 5-minute capillary acid absorption height and pressurized acid absorption performance, and its dynamic wet rebound performance is better than that of ordinary separators, which makes the cycle life of deep cycle power battery longer. Detailed Implementation
[0021] The technical solution of the present invention is illustrated below with specific embodiments, but the scope of protection of the present invention is not limited thereto: General Implementation Examples A composite separator suitable for deep-cycle power lead-acid batteries includes a coarse cotton layer and a fine cotton layer. In the lead-acid battery, the coarse cotton layer faces the positive electrode, and the fine cotton layer faces the negative electrode. By weight percentage, the raw materials of the coarse cotton layer include 39–49% 17°SR glass fiber cotton (diameter range 2–4 μm), 25–30% 24°SR glass fiber cotton (diameter range 2.5–3 μm), 5–8% reinforcing fibers (glass fiber with a diameter of 9 μm), and 20–30% fine cotton layer raw materials or recycled components. The recycled components are the product of recycling discarded composite separators. The maximum pore size of the coarse cotton layer is 42–45 μm.
[0022] By weight percentage, the raw materials of the fine cotton layer include 40–44% 44°SR glass fiber cotton (diameter range 0.3–1 μm), 50–54% 29°SR glass fiber cotton (diameter range 2–2.5 μm), 2–4% PET fiber, and <6% reinforcing fiber. The pore size of the fine cotton layer is 12–15 μm.
[0023] Ultimately, the thickness of the fine cotton layer accounts for 1 / 3 to 2 / 3 of the total thickness of the composite partition.
[0024] The preparation method of the above-mentioned composite separator includes the following steps: (1) The raw materials of the coarse cotton layer and the fine cotton layer are mixed and pulped separately in different pulping tanks; (2) The coarse cotton layer slurry and the fine cotton layer slurry obtained in step (1) are vibrated and compounded at a water content of 99%, and then formed on a molding net to obtain a composite partition.
[0025] Example 1 A composite separator suitable for deep-cycle power lead-acid batteries includes a coarse cotton layer and a fine cotton layer. In the lead-acid battery, the coarse cotton layer faces the positive electrode, and the fine cotton layer faces the negative electrode.
[0026] By weight percentage, the raw materials of the fine cotton layer include 42% 44°SR glass fiber cotton, 51% 29°SR glass fiber cotton, 3% PET fiber, and 4% reinforcing fiber. The pore size of the fine cotton layer is 12–13 μm.
[0027] By weight percentage, the raw materials of the coarse cotton layer consist of 43% 17°SR glass fiber cotton, 26% 24°SR glass fiber cotton, 6% reinforcing fibers, and 25% fine cotton layer raw materials (including 42% 44°SR glass fiber cotton, 51% 29°SR glass fiber cotton, 3% PET fibers, and 4% reinforcing fibers). The maximum pore size of the coarse cotton layer is 45 μm.
[0028] The composite partition is 1.50 mm thick, with the fine cotton layer being 0.52 mm thick.
[0029] The preparation method of the above-mentioned composite separator includes the following steps: (1) The raw materials of the coarse cotton layer and the fine cotton layer are mixed and pulped separately in different pulping tanks; (2) The coarse cotton layer slurry and the fine cotton layer slurry obtained in step (1) are vibrated and compounded at a water content of 99%, and then formed on a molding net to obtain a composite diaphragm.
[0030] Example 2 A composite separator suitable for deep-cycle power lead-acid batteries includes a coarse cotton layer and a fine cotton layer. In the lead-acid battery, the coarse cotton layer faces the positive electrode, and the fine cotton layer faces the negative electrode.
[0031] By weight percentage, the raw materials of the fine cotton layer include 40% 44°SR glass fiber cotton, 54% 29°SR glass fiber cotton, 2% PET fiber, and 4% reinforcing fiber. The pore size of the fine cotton layer is 13–14 μm.
[0032] By weight percentage, the raw materials of the coarse cotton layer consist of 48% 17°SR glass fiber cotton, 26% 24°SR glass fiber cotton, 6% reinforcing fibers, and 20% fine cotton layer raw materials (including 40% 44°SR glass fiber cotton, 54% 29°SR glass fiber cotton, 2% PET fibers, and 4% reinforcing fibers). The maximum pore size of the coarse cotton layer is 44 μm.
[0033] The composite partition is 1.50 mm thick, with the fine cotton layer being 0.60 mm thick.
[0034] The preparation method of the above-mentioned composite separator includes the following steps: (1) The raw materials of the coarse cotton layer and the fine cotton layer are mixed and pulped separately in different pulping tanks; (2) The coarse cotton layer slurry and the fine cotton layer slurry obtained in step (1) are vibrated and compounded at a water content of 99%, and then formed on a molding net to obtain a composite partition.
[0035] Example 3 A composite separator suitable for deep-cycle power lead-acid batteries includes a coarse cotton layer and a fine cotton layer. In the lead-acid battery, the coarse cotton layer faces the positive electrode, and the fine cotton layer faces the negative electrode.
[0036] By weight percentage, the raw materials of the fine cotton layer include 44% 44°SR glass fiber cotton, 50% 29°SR glass fiber cotton, 3% PET fiber, and 3% reinforcing fiber. The pore size of the fine cotton layer is 14–15 μm.
[0037] By weight percentage, the raw materials of the coarse cotton layer consist of 40% 17°SR glass fiber cotton, 28% 24°SR glass fiber cotton, 7% reinforcing fibers, and 25% fine cotton layer raw materials (including 44% 44°SR glass fiber cotton, 50% 29°SR glass fiber cotton, 3% PET fibers, and 3% reinforcing fibers). The maximum pore size of the coarse cotton layer is 42 μm.
[0038] The composite partition is 1.50 mm thick, with the fine cotton layer being 0.65 mm thick.
[0039] The preparation method of the above-mentioned composite separator includes the following steps: (1) The raw materials of the coarse cotton layer and the fine cotton layer are mixed and pulped separately in different pulping tanks; (2) The coarse cotton layer slurry and the fine cotton layer slurry obtained in step (1) are vibrated and compounded at a water content of 99%, and then formed on a molding net to obtain a composite partition.
[0040] Example 4 A composite separator suitable for deep-cycle power lead-acid batteries includes a coarse cotton layer and a fine cotton layer. In the lead-acid battery, the coarse cotton layer faces the positive electrode, and the fine cotton layer faces the negative electrode.
[0041] By weight percentage, the raw materials of the fine cotton layer include 42% 44°SR glass fiber cotton, 51% 29°SR glass fiber cotton, 3% PET fiber, and 4% reinforcing fiber. The pore size of the fine cotton layer is 12–13 μm.
[0042] By weight percentage, the raw materials of the coarse cotton layer include 43% 17°SR glass fiber cotton, 26% 24°SR glass fiber cotton, 6% reinforcing fiber, and 25% recycled material (the recycled material is the product of the recycled composite partition from Example 1 after it has been scrapped and recycled). The maximum pore size of the coarse cotton layer is 45 μm.
[0043] The composite partition is 1.50 mm thick, with the fine cotton layer being 0.52 mm thick.
[0044] The preparation method of the above-mentioned composite separator includes the following steps: (1) The raw materials of the coarse cotton layer and the fine cotton layer are mixed and pulped separately in different pulping tanks; (2) The coarse cotton layer slurry and the fine cotton layer slurry obtained in step (1) are vibrated and compounded at a water content of 99%, and then formed on a molding net to obtain a composite diaphragm.
[0045] Comparative Example 1 Standard partition (Changzhou Haixin AGM partition 1.52×72) Comparative Example 2 The difference from Example 1 is that the composite partition contains only a fine cotton layer.
[0046] The composite separator includes a fine cotton layer. By weight percentage, the fine cotton layer consists of 42% 44°SR glass fiber cotton, 51% 29°SR glass fiber cotton, 3% PET fiber, and 4% reinforcing fiber. The pore size of the fine cotton layer is 13–14 μm.
[0047] The thickness of the composite partition is 1.50 mm.
[0048] The preparation method of the above-mentioned composite separator includes the following steps: (1) In the pulping tank, the raw materials of the fine cotton layer are mixed and pulped; (2) The fine cotton layer slurry obtained in step (1) is formed on a molding mesh with a water content of 99% to obtain a composite diaphragm.
[0049] Comparative Example 3 The difference from Example 1 is that the composite partition only contains a coarse cotton layer.
[0050] The composite partition includes a coarse cotton layer. By weight percentage, the raw materials of the coarse cotton layer include 43% 17°SR glass fiber cotton, 26% 24°SR glass fiber cotton, 6% reinforcing fiber, and 25% fine cotton layer raw materials (including 42% 44°SR glass fiber cotton, 51% 29°SR glass fiber cotton, 3% PET fiber, and 4% reinforcing fiber).
[0051] The thickness of the composite partition is 1.50 mm.
[0052] The preparation method of the above-mentioned composite separator includes the following steps: (1) In the pulping tank, the raw material of the coarse cotton layer is mixed and pulped; (2) The coarse cotton slurry obtained in step (1) is formed on a molding mesh with a water content of 99% to obtain a composite diaphragm.
[0053] Table 1 As shown in Table 1, by adjusting and optimizing the cotton composition, ratio, and thickness ratio of the coarse and fine cotton layers in the composite separator, the capillary action on the XY plane of the separator achieves better acid regulation, and the uniformity of acid distribution in the upper, middle, and lower parts of the composite separator is also improved. Comparative Example 1 shows that, compared with ordinary separators, this composite separator has superior 5-minute capillary acid absorption height and pressurized acid absorption performance, as well as better dynamic wet resilience, resulting in a longer cycle life for deep-cycle power batteries. Comparative Examples 2-3 show that the cotton composition, ratio, and thickness ratio of the coarse and fine cotton layers in the composite separator of this invention all affect acid regulation performance, acid absorption performance, and resilience.
[0054] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made using the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A composite separator suitable for deep-cycle power lead-acid batteries, characterized in that, It includes a coarse cotton layer and a fine cotton layer; the coarse cotton layer faces the positive electrode of the battery, and the fine cotton layer faces the negative electrode of the battery. By weight percentage, the raw materials of the coarse cotton layer include 39-49% 17°SR glass fiber cotton, 25-30% 24°SR glass fiber cotton, 6-8% reinforcing fiber, and 20-30% fine cotton layer raw materials; the maximum pore size of the coarse cotton layer is 42-45 μm. By weight percentage, the raw materials of the fine cotton layer include 40-44% 44°SR glass fiber cotton, 50-54% 29°SR glass fiber cotton, 2-4% PET fiber, and <6% reinforcing fiber; the pore size of the fine cotton layer is 12-15μm.
2. The composite separator for deep-cycle power lead-acid batteries as described in claim 1, characterized in that, By weight percentage, the raw materials of the fine cotton layer include 42% 44°SR glass fiber cotton, 51% 29°SR glass fiber cotton, 3% PET fiber and 4% reinforcing fiber.
3. The composite separator for deep-cycle power lead-acid batteries as described in claim 2, characterized in that, By weight percentage, the raw materials of the coarse cotton layer include 43% 17°SR glass fiber cotton, 26% 24°SR glass fiber cotton, 6% reinforcing fiber, and 25% fine cotton layer raw materials.
4. The composite separator for deep-cycle power lead-acid batteries as described in claim 1, characterized in that, By weight percentage, the raw materials of the fine cotton layer include 40% 44°SR glass fiber cotton, 54% 29°SR glass fiber cotton, 2% PET fiber and 4% reinforcing fiber.
5. The composite separator for deep-cycle power lead-acid batteries as described in claim 4, characterized in that, By weight percentage, the raw materials of the coarse cotton layer include 48% 17°SR glass fiber cotton, 26% 24°SR glass fiber cotton, 6% reinforcing fiber, and 20% fine cotton layer raw materials.
6. The composite separator for deep-cycle power lead-acid batteries as described in claim 1, characterized in that, By weight percentage, the raw materials of the fine cotton layer include 44% 44°SR glass fiber cotton, 50% 29°SR glass fiber cotton, 3% PET fiber and 3% reinforcing fiber.
7. The composite separator for deep-cycle power lead-acid batteries as described in claim 6, characterized in that, By weight percentage, the raw materials of the coarse cotton layer include 40% 17°SR glass fiber cotton, 28% 24°SR glass fiber cotton, 7% reinforcing fiber, and 25% fine cotton layer raw materials.
8. The composite separator for deep-cycle power lead-acid batteries as described in claim 1, characterized in that, The thickness of the fine cotton layer accounts for 1 / 3 to 1 / 2 of the total thickness of the composite partition.
Citation Information
Patent Citations
preparation method of an AGM separator with low resistivity
CN109273642A
Storage battery composite separator and preparation method thereof
CN108539111A
Lead accumulator utmost point crowd
CN208570747U